An evaluation of thiol/disulphide homeostasis in patients with psoriasis - Kilic, Arzu; Yorulmaz, Ahu; Erdogan, Serpil; Cakmak, Seray Kulcu; Guney, Elif; Sen, Orhan; Erel, Ozcan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : The role of oxidative stress in the pathogenesis of psoriasis has been investigated in previous studies with conflicting results. On the other hand, well-established treatments currently used in psoriasis exert their effects via a boost of oxidative stress. Recently, a strong positive association between psoriasis, metabolic syndrome and dyslipidemia has also been described showing the complex nature of the disease. Aim : To examine thiol/disulphide homeostasis, a newly developed homeostasis assay in psoriasis and evaluate the possible association between thiol/disulphide homeostasis and dyslipidemia in psoriasis. Material and methods : The study population included 92 psoriasis patients and 71 healthy subjects. Serum native thiol, total thiol and disulphide levels were investigated in patients with psoriasis and in healthy subjects. In addition, lipid profile (serum total cholesterol, triglyceride, high-density lipoprotein cholesterol and low-density lipoprotein cholesterol) levels were investigated in both groups. The association between thiol-disulphide parameters and dyslipidemia was also evaluated. Results : Serum total cholesterol and triglyceride levels were found to be higher in patients with psoriasis than in the healthy group. Lower plasma disulphide and higher native thiol levels were found in patients with psoriasis indicating an antioxidant status. Conclusions : To our knowledge, this is the first study showing the shift of dynamic thiol/disulphide homeostasis towards the thiol form in psoriasis which indicate higher antioxidant status.